Potential role of macrophages as immunoregulators of pregnancy - Abrahams Vikki M; Mor Gil (BMC, 2003)
Abstract The role of the maternal immune system during pregnancy has focused mainly on the aspect of immune tolerance to the invading trophoblast and, therefore, fetus. While this is a critical aspect of reproductive immunology, it is also important to consider the function of the maternal immune system in the promotion of implantation and maintenance of pregnancy. Apoptosis or cell death is not the final stage in tissue development. The quick and effective removal of apoptotic cells by tissue macrophages represents a vital process preventing "leak" of self-antigens and promoting the production of proliferative/survival factors. One of the key requirements of apoptotic cell clearance is the resolution of inflammatory conditions, which, as in the case of pregnancy, may have lethal consequences. This review will focus on decidual macrophages and their role on apoptosis and cell clearance during pregnancy.